PENGARUH PENGGUNAAN LIMBAH AMPAS TEBU (BAGASSE ASH) SEBAGAI BAHAN POZZOLAN PADA BETON RINGAN - Alfain, M. Hifzni; Mulyati, Ely (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
This study aims to analyze the effect of using sugarcane bagasse ash (BA) as a partial substitute for cement in lightweight concrete mixtures. The experimental method was conducted with variations of BA substitution at 0% (normal), 2.5%, 3.5%, and 4.5% of the cement weight. The tests included slump test, compressive strength at 7, 21, and 28 days, and split tensile strength at 28 days. The results showed that the use of BA up to 4.5% still met the workability requirements according to SNI 1972:2008 with slump values ranging from 7.2-8.2 cm. The optimal compressive strength was achieved at 3.5% BA substitution with values of 8.77 MPa (7 days), 26.31 MPa (21 days), and 28.58 MPa (28 days), representing an increase of 14.8%, 9.0%, and 7.1% respectively compared to normal concrete. Similarly, the split tensile strength reached its highest value of 2.36 MPa at 3.5% BA substitution. The study concludes that 3.5% BA substitution is the optimal proportion for producing lightweight concrete with improved mechanical properties while maintaining good workability.Keywords: compressive strength, lightweight concrete, pozzolan, split tensile strength, sugarcane bagasse ash